UPAYA MENINGKATKAN HASIL BELAJAR SISWA MATERI SUMBER DAYA ALAM MELALUI MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA SISWA KELAS III SD NEGERI SUAK PUNTONG - Muttaqin (LPPM Universitas Cipta Mandiri, 2025)
This research aims to describe the application of the Contextual Teaching and Learning (CTL) learning model which can improve student learning outcomes and to describe student learning outcomes regarding natural resources through the Contextual Teaching and Learning (CTL) learning model in class III students at SD Negeri Suak Puntong Regency Nagan Raya. The type of research used is classroom action research. The subjects taken in this research were all class III students at SD Negeri Suak Puntong, Nagan Raya Regency, with a total of 15 students. The results of this research can be concluded that the application of the Contextual Teaching and Learning (CTL) learning model in this research is constructivism, namely the teacher directs students, teacher investigation motivates students, questioning questions and answers with students, learning community students are divided into several study groups, teacher modeling acts as models for students, reflection guiding the learning that has been carried out, and authentic assessment, namely assessing student learning outcomes. The application of the Contextual Teaching and Learning (CTL) learning model is very effective in improving student learning outcomes in natural resource material in class III of SD Negeri Suak Puntong. In the pre-cycle there were 2 students who completed it or (13.33%), while in the first cycle there were 7 students who completed it or (46.67%). Furthermore, cycle II showed a very significant increase in student learning outcomes, namely there were 13 students who completed it or (86.67%).